The Effect of Service Quality and Perception of Values for Behavior In UPBJJ-UT Denpasar: The Role of Customer Satisfaction Mediation - Wahyudi , Heri; Sudrajat; Wiyarni, Arti (International Journal of Psychosocial Rehabilitation, 2020)
This research is a quantitative research that aims to analyze the effect of service quality, perceived value on intention to behave by mediating customer satisfaction. The context of this research is the education sector that provides services to students. This research is important because the four constructs are interconnected. The respondents of this study were students of the UPBJJ-UT Non-Public Relations Program Denpasar. The benefits of this study are expected to provide input on policies related to service to students. To measure the construct of service quality, perceived value, customer satisfaction and intention to behave using a questionnaire whose indicators are adapted from ISO standards JJ02-RK01a-Ed.2 and interviews with several respondents. Before this instrument is used to measure all four constructs, the validity and reliability are tested first so that the results of the study are more accurate. To analyze the data obtained from respondents, researchers conducted an analysis using confirmatory factor analysis to confirm the factors that shape the construct of service quality, perceived value, customer satisfaction and intention to behave. Whereas to determine the influence of service quality and perceived value on intention to behave by mediating customer satisfaction using linear regression. The results of this study indicate that service quality directly and positively affects customer satisfaction. Value perception directly and positively affects customer satisfaction. Customer satisfaction directly and positively affects the intention to behave. Service quality and perceived value through mediating customer satisfaction positively affects intention to behave.